Moral economy: Rethinking a radical concept - Palomera, Jaime; Vetta, Theodora (Anthropological Theory, 2016)
This article argues that the original thrust of the moral economy concept has been understated and attempts to cast it in a new light by bringing class and capital back into the equation. First, it reviews the seminal works of Thompson and Scott, tracing the origins of the term. It deals with the common conflation of moral economy with Polanyi’s notion of embeddedness, differentiating the two concepts and scrutinizing the ways in which these perspectives have been criticized. Second, it dispels dichotomist conceptions separating economic practice from morality, or embedded configurations from disembedded ones. Against binary views of the market as a boundless realm penetrating previously untainted moral spheres, it posits that social reproduction is characterized by an entanglement of values, which can only be fully grasped by delineating the contours and characteristics of capital accumulation. Third, it contends that moral economy is a dynamic concept because it accounts for class-informed frameworks involving traditions, valuations and expectations. Finally, it argues that moral economy can enrich the concept of hegemony because it pays attention to the often-contradictory values that guide and sustain livelihood practices, through which cultural domination is reproduced or altered.
Keywords: SCOTT, James C.; THOMPSON, E.P.; capital; class; economics - moral & ethical aspects; embeddedness; hegemony; moral economy; saving and investment; social reproduction

Expanding the labor theory of value - Collins, Jane (Dialectical Anthropology, 2016)
This paper revisits debates over the labor theory of value in the 1970s and 1980s and proposes an expansion and revision for the neoliberal era. It draws on three empirical cases of social movements grappling with contemporary changes in the societal division of labor and argues that they can best be understood as 'revaluation' projects seeking to bring recognition to aspects of the economy that are necessary for its long-term sustainability but are not 'counted' as important.
Keywords: division of labor; domestic labor; environment; feminism; labor theory of value; labour theory of value; neoliberalism; public sector; shareholder value; social movements; sustainability

A Concept of Eurasia - Hann, Chris (Current Anthropology, 2016)
To imagine Europe and Asia as constituting equivalent "continents" has long been recognized as the ethnocentric cornerstone of a Western, or Euro-American, world view. The amalgam Eurasia corrects this bias by highlighting the intensifying interconnectedness of the entire landmass in recent millennia. This article builds on the work of Jack Goody and others to analyze the unity-in-civilizational-diversity of the Old World. It draws on the substantivist economic anthropology of Karl Polanyi to postulate continuities between ancient ideals of economic embeddedness in the agrarian empires and various forms of socialism in the twentieth century. Today, when the human economy everywhere is again exposed to the domination of the market, the Eurasian dialectic has universal relevance. However, recognition and realization of pan-Eurasian affinities continues to be impeded by geopolitics, and sociocultural anthropology has a long way to go to overcome its Atlantic bias.
Keywords: Eurasia; GOODY, Jack, 1919-2015; economic anthropology; ethnocentrism; geopolitics; socialism; substantivist

"Let Them Eat Stuffed Peppers": An Argument of Images on the Role of Food in Understanding Neoliberal Austerity in Greece - Sutton, David (Gastronomica, 2016)
This paper focuses on how discourses of food have shaped understandings of what is at stake in the Greek crisis. Drawing from Karl Polanyi's concept of "embeddedness," I argue that food is central to Greek interpretations of neoliberal policies and processes because of its centrality to Greek culture and identity. Food has also been a site of contested practices of "solidarity" and "charity" by which new social experiments are emerging in the wake of the breakdown of the welfare state. In arguing for food's centrality in the reshaping of Greek sociability, I will suggest that food be thought of not simply as a "topic" for anthropological investigation, but as a master-concept on the level of "kinship," "ritual," or "exchange" in any anthropological analysis of contemporary life.
Keywords: Greece; Greek crisis; Kalymnos; Oriental and African Studies; austerity (economics); critical food studies; food metaphors; food studies; kinship; neoliberalism; solidarity

Local Trade and Exchange/Employment Systems (LETS) in Future Eco-sustainable Societies - Westra, Richard (Anthropology in Action, 2016)
All communities of practice must face questions relating to the material economic foundations of future sustainable societies. David Graeber, Karl Polanyi and Karl Marx each have produced typologies of possible types of economy, synthesised as: (1) the principle of individual reciprocity, (2) the market principle of capitalism, and (3) the planning principle of the state. I apply this synthesis to recent proposals for community change advanced by Bill McKibben and David Korten concerning economic scale and the re-localising of production and consumption sundered by globalisation, focused on the local exchange and trading system (LETS). The operationalising of LETS draws upon Adam Smith's view of markets as face-to-face exchanges of goods taking place in small morality-bound communities. Smith, McKibben and Korten conflate two different meanings of the term 'exchange'. To understand the role LETS may play in future sustainable economies in communities of practice demands treatment of this problem.
Keywords: MCKIBBEN, Bill, 1960-; capitalism; communities of practice; community; eco-sustainability; economy; globalization; local exchange and trading systems; markets; sustainability; sustainable societies

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare